Position Of The Deed Of Will Made By Notary In Dispute Between The Heirs (Case Study Of Religion Court Decision No. 0427/Pdt.G/2014/PA.bla) - Nurul Kusumawati; Akhmad Khisni (Jurnal Akta, 2018)
An inheritor can make a deed of will before a Notary, so that in a dispute occur later on between the heirs, the deed of will can be used as a basis for deciding the dispute between parties. Notaries who have the authority to make a deed of will have the obligation to serve the community in making a deed of will in the form of an authentic deed as stipulated in Article 15 paragraph (1) of Law Number 2 year 2014 concerning Amendments to Law Number 30 on the Position of Notary, which reads " The Notary has the authority to make authentic deeds regarding all deeds, agreements, and stipulations required by legislation and/or desired by the interested parties to be stated in an authentic deed, to guarantee certainty of the date of making the deed, to store the deed, give grosse, copy and quote of deed. All of those matters can be done by the notary as long as the deed is not also assigned or excluded to other officials or other people determined by law". So it is expected that the will certificate in the form of an authentic deed made by a notary based on the will of the inheritor can provide a solution that can be used as a basis in deciding a case of dispute between heirs. Legally, the heirs have secured the right as an heir, in accordance with Article 874 of the Civil Code. Related to the dispute between the heirs caused by the will deed made by the Notary, the Court take responsibility to overcome the dispute, so that all parties can get legal certainty.Keywords: Testament Deed, Authority of Notary, Dispute of Heirs